The Effect of Profit Management and Good Corporate Governance Managerial Performance with The Quality of Management Accounting Information System as a Moderating Variabel at Pt. Indonesian Port (Persero) Regional 1 - Rialdy, Novien; Farzransyah, Muammar (Journal of International Conference Proceedings, 2025)
The purpose of this study is to test and analyze the effect of Earnings Management and Good Corporate Governance on managerial performance with the Quality of Management Accounting Information Systems as a moderating variable at PT Indonesian Port (Persero) Regional I. The approach used in this study is an associative approach. The population in this study were all employees of PT Indonesian Port (Persero) Regional I. The data collection technique in this study used observation and questionnaire techniques. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study used the PLS (Partial Least Square) software program. The results of this study prove that Earnings Management directly has a significant effect on managerial performance. Good Corporate Governance has a significant effect on managerial performance with the Quality of Management Accounting Information Systems as a Moderating Variable at PT Indonesian Port (Persero) Regional I